Use of essential oils in poultry nutrition: A new approach (Journal of Advanced Veterinary and Animal Research, 2014)
Emergence of antibiotic resistant bacteria has created the necessity of replacement of antibiotic with other products like prebiotics, probiotics, organic acid botanicals, and herbal essential oils. Essential oils (EOs) are important aromatic components of herbs and spices, and are used as natural alternatives for replacing antibiotic growth promoters (AGPs) in poultry feed as these have antimicrobial, antifungal, antiparasitic, and antiviral properties. Beside, other beneficial effects of EOs include appetite stimulation, improvement of enzyme secretion related to food digestion, and immune response activation. Recently, use of EOs in broiler chickens has drawn attentions. EOs are generally used as blend with a carrier oil or combination with other plant oils in the feed to enhance the productive performance of birds. Conclusively, EOs can be used in poultry feed, but there are still questions concerning their action, metabolic pathway and optimal dosage in poultry, which are to be explored in detail. This mini-review describes the expanding horizons in the research on EOs in poultry nutrition.   http://dx.doi.org/10.5455/javar.2014.a36